Unsettling planning theory. (August 2018) - Barry, Janice; Horst, Megan; Inch, Andy; Legacy, Crystal; Rishi, Susmita; Rivero, Juan J; Taufen, Anne; Zanotto, Juliana M; Zitcer, Andrew
Recent political developments in many parts of the world seem likely to exacerbate rather than ameliorate the planetary-scale challenges of social polarization, inequality and environmental change societies face. In this unconventional multi-authored essay, we therefore seek to explore some of the ways in which planning theory might respond to the deeply unsettling times we live in. Taking the multiple, suggestive possibilities of the theme of unsettlement as a starting point, we aim to create space for reflection and debate about the state of the discipline and practice of planning theory, questioning what it means to produce knowledge capable of acting on the world today. Drawing on exchanges at a workshop attended by a group of emerging scholars in Portland, Oregon in late 2016, the essay begins with an introduction section exploring the contemporary resonances of 'unsettling' in, of and for planning theory. This is followed by four, individually authored responses which each connect the idea of unsettlement to key challenges and possible future directions. We end by calling for a reflective practice of theorizing that accepts unsettlement but seeks to act knowingly and compassionately on the uneven terrain that it creates.